(3ebGdI aj CZQGV cJGH eG HYO GdWHjYIs - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s
(3ChdgG (B:s
(3bGd bUOfG ai gPg GdebGdI gh Cf fOd Ydi GdZQV GdPi jTJed Ydjg cJGH CQSWhWGdjS GdeYQha HeG HYO GdWHjYI s
(3BNQgG (B:s
(3hGdebGdI GdKGfjI YTQ ai eHGOi GdWHjYjGJ hGdJYdjeGJ agPg gi GdGHGfI Yf ZQV gPG GdcJGH hYf GbSGeg JeJ GdebGdI hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3hQO GdYfhGf GdCUdi ai cX (B2/ 1455s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(1/240) s
Keywords: (3GdadSaI hGdefWbs